Pigmented Basal Cell Carcinoma of Nipple and Areola in a Male Breast - A Case Report with Review of Literature - Kalyani, R. (Master Publishing Group, 2014)
Basal cell carcinoma is a common skin cancer worldwide. However basal cell carcinoma of nipple and areola complex is rare, commonly seen in males in elderly age group. The tumor has aggressive behavior with increased tendency for metastasis. We present a case in a 78 year male in the left breast.